Ensino de leitura de sentenças para crianças em idade escolar - Donadeli, Josiane Maria (2016)
Several teaching procedures based on the stimulus equivalence paradigm have been developed and proved effective in improving reading performance. Expanding the research on the subject, this study aimed to determine the effects of using a teaching reading sentences procedure with this paradigm. The study used programmed sentences with multiple and critical differences in order to check, as a secondary measure, possible patterns of responding under the control of stimuli in this situation and the effects of these patterns on learning to read. The sentences were composed of subject, verb and object. Ten children with seven to nine years old, without clinical diagnosis, attending in the first primary education cycle, participated. The study consisted of four phases and 12 steps. The sentences and the difficulty of discrimination varied over the phases: simple words of the Portuguese language and comparisons had multiple differences between them; simple words and critical differences; complex words and multiple differences; and complex words and critical differences. The steps contemplated pretest and posttest, teaching AB relations (match figures to spoken sentences) and AC (match printed sentences to spoken sentences), testing of BD relations (nomination of the figure), CD (nomination of the printed sentence), BC (match printed sentences to the figures) and CB (match figures to the printed sentences), Reading Test of recombinative generalization sentences, Reading Test of comparisons sentences and test of learning maintenance after 30 days. Nine of ten participants had higher performance at posttest than in the pretest. The children had more errors in the phases that had critical differences. In the Reading Test of recombinative generalization sentences, two of ten children had a high percentage of correct answers. The results suggest that the procedure promoted the learning of sentences during the teaching; however, it was not sufficient for recombinative generalization.